Extreme maternal morbidity in peruvian women attended at a specialized institution. 2012-2016 - Gonzales-Carrillo, Oswaldo (2020)
Introduction: Extreme maternal morbidity generates indicators to assess and monitor the risk of maternal death. Objective: To describe the extreme maternal morbidity in Peruvian women attended in a specialized institution in Peru, 2012-2016. Material and Method: Observational, descriptive and transversal study. Patients attended at the National Maternal and Perinatal Institute, between 2012 and 2016 were included. Cases of extreme maternal morbidity were included according to criteria of the Latin American Federation of Obstetrics and Gynecology Societies. The study shows maternal characteristics and outcome indicators. Descriptive and inferential statistics were applied under 95% confidence intervals, using the Stata version 14. Results: The study population was 1245 cases. Multiparity was present in 63.7% of cases, presented on average 4 prenatal controls and 60% of cases had at least one previous cesarean section. The extreme maternal morbidity ratio varied between 10.7 and 17.6 per 1,000 live births, the mortality index was 3%, the extreme maternal morbidity / maternal mortality ratio was 32.8 cases. Conclusions: The average prevalence of extreme maternal morbidity was 13 cases per thousand live births with a tendency to increase in the last three years of the study, mainly due to hypertensive disorders, sepsis and hemorrhages. The outcome indexes of extreme maternal morbidity demonstrate a progressive improvement in the quality of care of patients with a tendency to decrease maternal death.